Pesan Moral Film Animasi Nussa dan Rara Pada Youtube Nussa Official - Desy Iin Amaliana (DIGICOM : Jurnal Komunikasi dan Media, 2022)
The research is entiled “Moral Message In Animated Film Nussa and Rara on Youtube Episode 1-15” which aims to find out the moral message in the film Nussa and Rara. The research method used was descriptive quantitative content analysis, namely analysis to describe in detail the scenes contained in the film “Nussa and Rara” with the Pro Social indicators proposed by Wisped and Bandura, this theory states that the Pro Social sub-indicators are selfless, helpful, warm, cooperative, empathetic, praising, advising, regret, politeness, and the Anti Social sub-indicators, namely threats, coercion, war, fighting, insulting, cursing, betrayal, disobedience, sneaking, angry and lying. In analyzing the data, the researscher acts directly as a coder who filss in the coding with the help of 2 other coders who act as comparators/judges. The results showed that Pro Social was greater, namely 93% than Anti Social, which was 7%. Of all the Pro Social sub indicators that have the most points, namely advising from coder 1 points 100%, coder 2 point 100%, coder 3 87%, while the Anti Social sub-indicators is angry from coder 1 points 20%, coder 2 points 7%, coder 3 13%. The results suggest that Pro Social is more dominant is advising, whereas Anti Social is more dominant is angry. It can be concluded that Nussa and Rara films have a more Pro Social tendency.